They made the movies : conversations with great filmmakers - Bawden, James; Miller, Ron, 1939- (Screen classics (Lexington, Ky.), 2023)
"For decades, James Bawden and Ron Miller have established themselves as maestros of provocative interviews, giving fans unmatched insights into the lives of Hollywood A-listers. In their fourth collection, the authors pay tribute to film pioneers who lit up Tinseltown from the 1930s through the 1960s. They Made the Movies features conversations with legendary directors who created many of film's all-time classics, including Frank Capra (It's A Wonderful Life, 1946), Richard Fleischer (20,000 Leagues Under the Sea, 1954), Alfred Hitchcock (Psycho, 1960), Ralph Nelson (Lilies of the Field, 1963), Robert Wise (The Sound of Music, 1965), and Chuck Jones (How the Grinch Stole Christmas! 1966). Tantalizing firsthand details about many acclaimed films are revealed, such as the revelation of Mervyn LeRoy's first-choice of lead actress for The Wizard of Oz ("Shirley Temple . . . but Shirley couldn't sing like Judy [Garland]"), Billy Wilder's insights on directing ("You have to be a sycophant, a sadist, a nurse, a philosopher"), and how megaproducer Hal B. Wallis purchased an unproduced play titled Everyone Comes to Rick's and transformed it into Casablanca ("The part [of Sam] almost went to Lena Horne, but I thought she was too beautiful"). The authors also celebrate the contributions of marginalized filmmakers such as Ida Lupino, James Wong Howe, Oscar Micheaux, and Luis Valdez, who prevailed in Hollywood despite the discrimination they faced throughout their careers. They Made the Movies appeals to film and television enthusiasts of all ages"--